Sports, Events and Facilities Rental System for Cameron Highland District Council - GOH, JIA XING; KASIM, SHAHREEN (Applied Information Technology And Computer Science, 2024)
The sports, events and facilities rental system is a rental system that is built for Cameron Highland District Council. The aim is to improve the rental process because they still use traditional ways to record the rental details manually. The system is developed to make the rental process easier. Users can rent the sports, events and facilities anywhere, anytime. Furthermore, the administrator can update and check the rental record easily. There are some problems with using traditional ways to record rental data which are data security, accuracy and reliability, and accessibility. The initiative of this system is motivated by the realization that the current system is frequently disjointed and lacks the cohesiveness required to offer users a seamless and practical experience. This web-based platform, designed with user-friendliness in mind, enables rental in a short time anywhere, anytime.